Removal of cadmium from water by CNT–PAC composite: effect of functionalization - AlSaadi, Mohammed A.; Mamun, Abdullah Al; Alam, Md Zahangir; Amosa, Mutiu Kolade; Atieh, Muataz Ali (World Scientic Publishing Company, 2016)
Cadmium (Cd2þ) is one of the toxic heavy metals that is frequently used in many industrial products. The wastewater from these industries and their products contains residual cadmium that are di±cult to be removed economically from the e®luent. Carbon nanotubes (CNTs) were synthesized in several batches and tested for their removal e±cacy with regards to cadmium removal from synthetic wastewater. Fixed catalyst chemical vapor deposition (FCCVD) reactor system was fabricated in the laboratory for the synthesis of CNTs on the powdered activated carbons (PACs). The PACs were impregnated with Fe3þ catalysts, and growth parameters such as, the reaction time, gas °ow rates and reaction temperature were optimized. The sorption capacity of the raw CNT–PAC was not satisfactory until the sorbents were functionalized which eventually led to high adsorption capacities. The surface properties of CNT–PAC were modi¯ed by oxidative functionalization using two di®erent methods: sonication with KMnO4 and re°uxing with HNO3 at 140C. KMnO4-treated CNT–PAC exhibited the highest sorption capacity for cadmium uptake which increased from 4.77 mg/g (untreated CNT–PAC) to 11.16 mg/g; resulting in Cd2þ removal e±ciency from 38.87% to 98.35%.